Research on the Preparation and Performance of Binary Modified Maltodextrin Water-Reducing Agent - Jingzhi Wu; Min Qiao; Zhifeng Lyu; Qianping Ran (Advances in Materials Science and Engineering)
Using maltodextrin (MD) of different dextrose equivalent (DE) values, 1,3-propanesultone, and maleic anhydride as raw materials, a novel binary modified maltodextrin (BMMD) was synthesized and further applied as a water-reducing agent. Its structure was characterized by Fourier transform infrared (FT-IR) and UV. The rheological behavior of the sample solution and strengths for concrete were also determined and the adsorption was tested by TOC. The influence of the process parameters to degree of substitution (DS) and the dosage on the fluidity of cement paste were investigated. The results show that the optimal conditions of sulfonation were the MD of DE 15, m (sulfonated agent)/m (MD) of 1.4, the catalyst amount of 1% by mass MD, and the reaction time of 12 h; the optimal conditions of esterification were m (esterified agent)/m (SMD) of 0.6, the reaction temperature of 90°C, and the reaction time of 4 h. The optimal dosages of sulfonated maltodextrin (SMD) and BMMD were 0.475% and 0.45%, respectively. In this dosage, the main dispersion capacity of BMMD attributes to two kinds of anchoring groups (SO3-  &  COO-) and the appropriate molecular weight of MD.